STUDIES ON CORRELATION AND CAUSE-EFFECT ANALYSIS IN RILS OF MTU 1010 X BR 2655 FOR YIELD AND NUTRITIONAL TRAITS IN RICE - RAMYA RATHOD; L.V.SUBBARAO; C. N. NEERAJA; K. B. ESWARI; D. SRINIVASA CHARY (The Bioscan, 2021)
The Research was conducted with an aim to study the character association and cause-effect analysis for yield, yield attributing and nutritional traits in 190 F 7 RILs derived from MTU-1010 and BR-2655 during Kharif 2016. Study revealed that panicle length (0.206*), productive tillers per plant (0.308*), filled grains per panicle (0.215*) and 1000-grain weight (0.307**) are positively associated with grain yield, indirect selection for these traits might improve the grain yield. Path analysis demonstrated that 1000-grain weight (0.367), plant height (0.129), filled grains per panicle (0.050), days to 50 per cent flowering (0.014) and productive tillers per plant (0.016) exerted positive direct effect on grain yield indicating that the selection for these characters was likely to bring about an overall improvement in grain yield per plant directly. These characters can be used in the selection programme to isolate superior lines with genetic potentiality for high yield in rice genotypes.